Knowledge, Attitudes, and Abilities of Pregnant Women with Chronic Energy Deficiency in Monitoring Prenatal Development - Syajaratuddur Faiqah; Ati Sulianty; Mutiara Rachmawati Suseno; Baiq Yuni Fitri Hamidiyanti (Indonesian Health Issue, 2026)
Background: Pregnancy is a crucial time during which the fetus grows and develops rapidly, both structurally and functionally in organs. Chronic energy deficiency (CED) among pregnant women in Indonesia is still high amounting to 17.3%. CED is known to impair fetal growth and development, as well as increase the risk of pregnancy complications. Objective: To determine the effect of the “monitoring card” educational tool on the knowledge, attitudes, and ability of pregnant women with CED to monitor their pregnancy progress. Methods: This study employed a quasi-experimental design with a non-equivalent pretest-posttest design. The population consisted of all pregnant women with CED in their third trimester within the service areas of the Dasan Tapen and Meninting Community Health Centers, with a total of 60 respondents. Sampling method used was purposive sampling with 30 samples in the intervention & 30 pregnant women in the control group. Mann-Whitney U test was used for the analysis. Results: The results of the statistical test showed the knowledge variable (p-value= 0.000), attitude variable (p-value= 0.001), and ability variable (p- value= 0.000). This means that Pregnancy Progress Monitoring Cards matter to pregnant women in the intervention and control groups per their knowledge, attitudes, and skills before and after the intervention. Conclusion: The use of educational media in the form of monitoring cards has a significant effect on improving the knowledge, attitudes, and skills of pregnant women with Chronic Energy Deficiency (CED) in monitoring their pregnancy progress.